CROSS-CULTURAL COMMUNICATION CHALLENGES IN INTERNATIONAL BUSINESS MANAGEMENT (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Cross-cultural communication is a critical component of effective international business management, yet it often presents significant challenges. This paper examines the main barriers that arise when individuals from diverse cultural backgrounds interact in global business environments, including differences in language, communication styles, values, negotiation patterns, and workplace norms. These challenges can lead to misunderstandings, reduced productivity, and weakened organizational relationships. The study emphasizes the importance of cultural intelligence, adaptive communication strategies, and inclusive leadership in mitigating these issues. Strengthening cross-cultural competence contributes to improved collaboration, smoother decision-making, and enhanced performance in multinational organizations.v